Corrective limb osteotomy using patient specific 3D-printed guides: A technical note. Issue 10 (October 2016) - Hoekstra, H.; Rosseels, W.; Sermon, A.; Nijs, S.
Abstract: We describe the step-by-step process of a corrective osteotomy using 3D printed patient specific guides. Before surgery, bilateral computed tomography (CT) scans are made to plan correction in the affected limb. The digital pre-planning defines the location of the K-wires, drill holes, and the osteotomy site(s). Subsequently, a 3D printed patient specific guide is applied, which indicates the exact position of these drill holes and the osteotomies. This increases the accuracy of the surgery by means of patient specific fit of the guide. During surgery an incision is made and the guide is applied on the bone, which allows the surgeon to perform a very precise osteotomy. Next, the bone is reduced either directly using the plate and marked drill holes, or indirectly using a second reduction guide. In the latter case, the previously drilled K-wires are used to adequately position the reduction guide. Fixation of the bone fragments using plating osteosynthesis finalizes the process. Although this technique has its specific limitations, it might serve as a powerful tool in the treatment of malunion of both articular and nonarticular fractures of the limb.